Biological Control Programmes in Canada 2001–2012 - Mason, P.G (CABI, 2014)
Biological control programmes in Canada continue to provide solutions for pest prob- lems that affect the food supply, our natural resources and the environment. These pro- grammes are aimed primarily at invasive alien species, which are increasingly disrupting the ability of Canadians to produce food, manage resources and enjoy their environment. This is the ﬁ fth volume in the series that summarizes the work on the many target species identiﬁ ed as important pests in Canada and covers the period 2001– 2012. During this time, studies on new pests have been initiated and studies on existing pests have continued. Most importantly, several projects are demonstrating clear suc- cess in reducing target pest numbers. The target species are primarily in agro-ecosys- tems, where activity has increased, while biological control activities in forest ecosystems have declined in the last 12 years. Biological control programmes against plant pathogens and annual weeds of crops continue to strengthen as our understanding of the complexities of plant–pathogen interactions increases. Great strides have been made in the development of inundative biological control agents that can be registered and used as commercial products. Several overview chapters are included in this volume to inform readers about emerging issues that will have an impact on biological control programmes in Canada. New research tools, such as molecular techniques, modelling and symbionts, and new approaches to organizing research that maximize resource investment, are beginning to facilitate biological control research as never before. Our understanding of how large- scale climate change will affect biological control is still in its infancy, but it is clear that there will be effects and that biological control programmes will have to adapt to these. In the past decade, greater regulatory constraints and implementation of inter- national agreements have presented new challenges, and by better understanding these, biological control programmes can continue to meet the needs of Canadians.